A new flame‐retardant medium density fiberboard with no formaldehyde release: Wood fiber cell walls template zeolite via in situ thermocompression. Issue 48 (24th July 2021) - Li, Ran; Feng, Lifei; Liang, Yuxin; Gao, Jie; Yang, Wenbin
Abstract: Fiberboard which is not flame retardant and releases formaldehyde is widely used in residents' life, which brings serious problems. Now, we use water glass and Al2 (SO4 )3 to form zeolite precursor, and use UP as adhesive to prepare zeolite‐based flame retardant formaldehyde‐free medium density fiberboard in situ within a few minutes. The molecular sieve structure was characterized by SEM, TEM, BET, and XRD. At the same time, we put forward the possible mechanism of zeolite formation according to the internal temperature and pressure test during fiberboard production. Wood fiber is coated with zeolite, which separates pyrolysis gas from air and avoids further combustion, resulting in low heat release, low smoke and toxic carbon monoxide emission, high residue, and good flame retardant performance. Furthermore, the formaldehyde emission of the formaldehyde‐free flame retardant board is 0.047 mg/L, which proves that it does not contain formaldehyde. Abstract : Wood‐based panels are widely used in interior decoration and furniture. They are flammable and release formaldehyde, which brings harm to the family. Through our research, we have made the medium density fiberboard with no formaldehyde release and flame retardant through in‐situ generated molecular sieve, which can effectively protect our home.